MENELUSURI MAKNA NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI (TRILOGI PERTAMA: CATATAN BUAT EMAK) - Chrisna Putri Kurniati (Balai Bahasa Provinsi Riau, 2012)
The main object of this research is Ahmad Toharis Ronggeng Dukuh Paruk. The purpose of this research is to expose the interpretation of the implicit message and add a depth appreciation of reading to literature in form of novel. This research aplies the theory of hermeneutic by using hermeneutic method. The result of this research shows that the novel reveals the tradition of ronggeng as a form of women exploitation. Besides, the tradition still glorifies animism and dynamism.